Use of space by laying hens: social and environmental implications for free-range systems - Grigor, Philip Norman (The University of Edinburgh, 1993)
The use of space by laying hens in free-range systems is often very uneven, with birds displaying an apparent reluctance to leave (and move away from) the house. Using mainly small groups as models for the larger flocks normally housed in commercial free-range systems, the role of various social and environmental factors concerning hens' movement and use of space were investigated in this thesis.

Hens displayed a greater readiness to emerge from a familiar covered box into an unfamiliar outdoor area when the outdoor area contained familiar feeders, even though the birds had free access to food in their home pens. Emergence latencies decreased with repeated testing. Birds also spent more time in the outdoor area when feeders were present, though they tended not to move past the feeder which was nearest the box. Birds which had been exposed to an enriching stimulus (traffic cones) in their home pens tended to leave the box earlier than those which had not, though this was not dependent on the actual presence of cones in the outdoor area. This suggests that a more complex home environment can influence birds' responses to novel environments. Furthermore, the order of emergence into the paddock was not significantly influenced by social rank. Birds which had been regularly exposed to the outside environment during the rearing process displayed little or no fear of the outdoor area as adults. In contrast, regular handling had little effect on birds' readiness to enter the outdoor area. Regular exposure to the outside environment also reduced birds' underlying fearfulness (measured by tonic immobility), both in small experimental groups and in a larger free-range flock. Individual birds from small groups or from single cages took longer to move past unfamiliar birds than they did to move past familiar birds (even those of higher rank), and took longer to move past an increasing number of unfamiliar birds. However, birds in a free-range house displayed a wide range of movements, and very little aggression, suggesting that any inhibition of movement within the house was not due to "pecking pressure" from other birds. Birds displayed greater readiness to enter into and disperse in the outdoor area when other birds were already present in the area. This was not dependent on the familiarity of birds in the outdoor area. A larger number of birds in the outdoor area increased the attractiveness of the outdoor area to other birds. The introduction of cover into an outside area had a limited effect on increasing the attractiveness of the outdoor area to domestic fowl, though this was not reflected in the birds' vigilance behaviour. It was concluded that birds find the outside environment aversive due to its fear-evoking properties (such as the fear of predation), and to the large discrepancy between the inside and outside environments. Possible implications of the present findings for free-range systems are discussed.